The Effect Of Tax Sanctions And Income Levels On Taxpayer Compliance With Awareness As Intervening Variables - Linda SOFIANA; Umi MUAWANAH; Kohar Adi SETIA (International Journal of Environmental, Sustainability, and Social Science, 2020)
The research objectives are: (1) to analyze the effect of tax sanctions, income levels and taxpayer awareness on taxpayer compliance. (2) to analyze the effect of tax sanctions and income levels on taxpayer awareness. (3) to analyze the effect of taxpayer awareness in mediating the effect of tax sanctions and income levels on taxpayer compliance. This research uses explanatory research type. The sample used is 75 individual taxpayer respondents at KPP Pratama Probolinggo. The statistical analysis used was the WarpPLS method. The result of the study indicates that: (1) There is no significant effect from tax sanctions upon the taxpayer compliance. (2) There are significant effect from income levels and taxpayer awareness upon the taxpayer compliance. (3) There are significant effect from tax sanctions and income levels upon the taxpayers awareness. (4)Taxpayer awareness cannot mediate the effect of tax sanctions and income levels on taxpayer compliance.